Evaluation of chain architectures and charge properties of various starch-based flocculants for flocculation of humic acid from water. (1st June 2016) - Wu, Hu; Liu, Zhouzhou; Yang, Hu; Li, Aimin
Abstract: Three different starch-based flocculants with various chain architectures and charge properties have been prepared through etherification, graft copolymerization, or their combination. Two of the flocculants (starch- graft -poly[(2-methacryloyloxyethyl) trimethyl ammonium chloride] and starch-3-chloro-2-hydroxypropyl triethyl ammonium chloride, denoted as STC- g -PDMC and STC-CTA respectively) are cationic, and another one (carboxymethyl starch- graft -poly[(2-methacryloyloxyethyl) trimethyl ammonium chloride], denoted as CMS- g -PDMC) is amphoteric. Those three flocculants have shown far different flocculation efficiency and floc properties for the removal of humic acid (HA) from water due to their distinct structural features. The effects of pH, flocculant dose, and initial HA concentration have been studied systematically. Accordingly, STC- g -PDMC and CMS- g -PDMC with strongly cationic branch chains have much better flocculation performance than polyaluminum chloride (PAC) and STC-CTA, the latter of which features linear chain architecture and strongly cationic pieces lying on its chain backbone. It indicates that the architecture of cationic branch chains plays an important role in HA flocculation due to their significantly enhanced bridging effects. Moreover, STC- g -PDMC has higher HA removal efficiency and better floc properties than CMS- g -PDMC, suggesting that charge neutralization effects make notable contributions to HA removal and that the additional anionic pieces on CMS- g -PDMC can weaken its flocculation performance. In addition, STC- g -PDMC used as coagulant aid for PAC has also been tried, which observably reduces the optimal dose of the inorganic coagulant. Graphical abstract: Highlights: Three different starch-based flocculants have been prepared. Those flocculants have various chain architectures and charge properties. Effects of chain architectures on flocculation of humic acid (HA) have been studied. Flocculants with cationic branch chains own better HA flocculation performance. Structure-activity relationship of starch-based flocculants has been built.